Involvement of regional lymph nodes after penetration of Schistosoma mansoni cercariae in naive and infected mice - Silene P Lozzi; Conceição RS Machado; Silvia E Gerken; Tomas A Mota-Santos (Memorias do Instituto Oswaldo Cruz, 1996)
The parotid lymph nodes of naive and previously infected Balb/c mice were studied after, respectively, infection and re-infection with cercariae of Schistosoma mansoni via the ears. Schistosomula were able to pass through the lymph node by following the lymph flow or by penetrating the veins of the medullary cords. The number of nodal mast cells was higher from day 2 to 6 of primary infection; and from day 5 to 11 of re-infection. The amount of degranulating mast cells was significantly higher at day 4 of infection and at day 1 of re-infection. Eosinophils characterized the nodal inflammatory processes observed after day 5 in both primarily-infected and re-infected mice. However, only in the latter the eosinophils were able to adhere to the larval surface. In primarily-infected mice, no intranodal larva presented signs of degeneration. In contrast, in re-infected animals, some degenerating larvae were found inside eosinophilic infiltrates. The eosinophils reached the nodal tissue by migrating through the high endothelial venules and their collecting veins.